Pengaruh Digital Marketing dan Brand Image terhadap Keputusan Pembelian melalui Minat Beli sebagai Intervening - Berlianda Tusamma Salsabila (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This research examines the influence of digital marketing and brand image on purchasing decisions through purchase interest as an intervening variable. The research focused on consumers of CMB skincare products at the Keyvalla Jombang Salon. The aim is to analyze the influence of digital marketing and brand image on purchasing interest and purchasing decisions. Using a quantitative approach, this research was conducted by distributing questionnaires to 200 respondents who had purchased CMB skin care products more than once. Data were analyzed using PLS-SEM to assess the relationship between variables. The findings reveal that digital marketing and brand image significantly influence purchasing interest and purchasing decisions. Apart from that, digital marketing and brand image have a direct impact on purchasing decisions and purchase intention which plays a mediating role. The results show that effective digital marketing and a strong brand image are critical to increasing consumer purchasing behavior in the skin care industry.